Topical anti-aging agents: state-of-the-art review - Prakoeswa, Flora Ramona Sigit; Maharani, Faradiba; Satria, Yohanes Aditya Adhi; Awanis, Ghina Shabrina; Febrianty, Astrida Fesky (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Skin aging can be divided into intrinsic and extrinsic aging. Even though it is inevitable, symptoms of skin aging are a common concern for patients. As a result, there is a surge in the making of anti-aging cosmeceuticals. However, there is a lack of evidence-based data to support the usage of topical preparations as anti-aging treatments. Therefore, further studies are needed to explore topical treatment options for skin aging. This literature review discusses the mechanism of commonly used topical anti-aging agents and their adverse reactions.